ChatGPT and Critical Thinking in Academic Writing: A Case Study of Indonesian Graduate Students - Duta Aisyah Pratiwi; Muhammad Tahir; Yunitari Mustikawati (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This qualitative case study investigates how three master students in the English Language Education Program at Universitas Negeri Makassar implement ChatGPT to support critical thinking in academic writing. Data were collected through triangulation of four sources, direct observations, semi-structured interviews, self-reflective journals, and documentation, and analyzed using Miles and Huberman's (1994) interactive model of data reduction, display, and conclusion drawing, guided by Paul and Elder's (2019) critical thinking framework and Hyland's (2018) academic writing framework. Findings reveal that students implement ChatGPT systematically across four writing stages: brainstorming and idea development, argument development and organization, information verification and validation, and comparative evaluation with traditional methods. The study's key contribution is its empirical demonstration that effective ChatGPT implementation functions as a cognitive scaffold that enhances rather than replaces critical thinking, provided students engage purposefully, verify outputs against academic sources, and adapt, rather than adopt, AI-generated content. These findings offer practical guidance for pedagogy and institutional policy on responsible AI integration in graduate academic writing.